Dose–Response of TLD-100 in the Dose Range Useful for Hypofractionated Radiotherapy. Issue 1 (11th February 2020) - Liuzzi, Raffaele; Piccolo, Consiglia; D'Avino, Vittoria; Clemente, Stefania; Oliviero, Caterina; Cella, Laura; Pugliese, Mariagabriella
Purpose: The aim of the study was to exploit the feasibility of thermoluminescent dosimeters (TLDs) in radiation therapy techniques in which high dose per fraction is involved. Methods: Dose–response of TLD-100 (LiF: Mg, Ti) was investigated in both 6-MV photon and 6-MeV electron beams. The element correction factor (ECF) generation method was applied to check the variability of the TLDs response. Two batches of 50 TLDs were divided into groups and exposed in the dose range 0 to 30 Gy. Regression analysis was performed with both linear and quadratic models. For each irradiation beam, the calibration curves were obtained in 3 dose range 0 to 8 Gy, 0 to 10 Gy, and 0 to 30 Gy. The best-fitting model was assessed by the Akaike Information Criterion test. Results: The ECF process resulted a useful tool to reduce the coefficients of variation from original values higher than 5% to about 3.5%, for all the batches exposed. The results confirm the linearity of dose–response curve below the dose level of 10 Gy for photon and electron beam and the supralinear trend above. Conclusion: The TLDs are suitable dosimeters for dose monitoring and verification in radiation treatment involving dose up to 30 Gy in a single fraction.